2015
DOI: 10.1063/1.4921813
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic properties of fcc Gd thin films

Abstract: Magnetic properties of sputtered Gd thin films grown on Si (100) substrates kept at two different temperatures were investigated using X-ray diffraction, ac magnetic susceptibility, and dc magnetization measurements. The obtained Gd thin films have a mixture of hcp and fcc structures, but with their fractions depending on the substrate temperature TS and film thickness x. Gd fcc samples were obtained when TS = 763 K and x = 10 nm, while the hcp structure was stabilized for lower TS (300 K) and thicker film (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…4 are obtained in fact for two different samples deposited under the same preparation conditions. Results showed that the Gd thin film grows in a mixture of f cc and hcp phases [21] as indicated in Fig. 4.…”
Section: Resultsmentioning
confidence: 98%
“…4 are obtained in fact for two different samples deposited under the same preparation conditions. Results showed that the Gd thin film grows in a mixture of f cc and hcp phases [21] as indicated in Fig. 4.…”
Section: Resultsmentioning
confidence: 98%
“…Note that most reports on lattice-expanded Gd are on thin-film specimen, where the level of control (regarding the quantity of expansion) is rather limited. For thin Gd films, the saturation magnetization was found to drop with increasing unit cell size 1 (strained hcp phase) or when obtaining Gd in other structural modifications ( fcc ) 26 . For a hydrogenated bulk specimen with rather large grains, strain and structural factors of thin films leading to the M s decrease are eliminated.…”
Section: Resultsmentioning
confidence: 99%
“…Поскольку оксиды гадолиния имеют чрезвычайно низкую температуру Кюри и не могут объяснять пика энтропии при 312 K [17], можно было бы принять во внимание сосуществование в микроструктурах двух ферромагнитных фаз гадолиния hcp и fcc [11]. Однако температура Кюри fcc-фазы составляет 280−285 K [11] (т. е. меньше, чем температура Кюри основной hcp-фазы), и поэтому наличие этой метастабильной фазы не может объяснять пик энтропии при 312 K.…”
Section: Discussionunclassified